Use of Joint-resident Mesenchymal Stromal Cells for Articular Cartilage Repair in Degenerative Knee Osteoarthritis - Hsiu-Jung Liao; Chih-Hung Chang (Formosan Journal of Musculoskeletal Disorders)
Osteoarthritis (OA) is an age-related disorder that causes painful and disabling joint pathologies and cartilage deterioration. Therapies based on mesenchymal stromal cells (MSCs) offer a novel regenerative treatment option for patients with knee OA. Joint-resident MSCs reside in joint and bone cavity niches, including the bone marrow, synovium, synovial fluid, and adipose tissue; these are primary MSC sources that are abundant in vivo and occupy multiple niches, making them ideal channels for therapeutic interventions against OA. MSCs migrate adjacent to the joint cavity during embryogenesis and provide crucial support for chondrogenesis. In adulthood, joint-resident MSCs serve as primary drivers of cartilage repair, and MSC reservoirs can be utilized for treating human articular cartilage injury because of their high cartilaginous production. This review summarizes the features of joint-resident MSCs and focuses on their application in therapies for knee OA.